GSI CTA evaluation of the vertebrobasilar artery in normal adults at high altitude - Wei, Jia; Hu, Huiying; He, Xin; Bao, Haihua (Frontiers in Cardiovascular Medicine, 2023)
Objective: Vascular geometry is affected by many factors during its growth and development. Here, we compared the differences in vertebrobasilar geometry among residents of plateau region at different altitudes, and investigated the relationship between vascular geometry and altitude. Methods: Adults in the plateau region with vertigo and headache as the main symptoms but no obvious abnormalities in imaging examination were collected. They were divided into 3 groups according to the altitude gradient, group A (18002500 masl), group B (25003500 masl), and group C (above 3500 masl), underwent head-neck energy spectral CTA with GSI scanning protocol. The following indices were observed: (1) Vertebrobasilar geometric configurations: Walking, Tuning Fork, Lambda, No Confluence. (2) Vertebral artery (VA) hypoplasia. (3) The bending number of bilateral VA intracranial segment. (4) Basilar artery (BA) length and tortuosity. (5) Anteroposterior (AP)MidBA angle, BAVA angle, LateralMidBA angle and VAVA angle. Results: Of the 222 subjects, 84 in group A, 76 in group B, and 62 in group C. The number of people in Group Walking, Tuning Fork, Lambda and No Confluence was 93, 71, 50 and 8, respectively. With the increase in altitude, the tortuosity of BA increased(1.05 ± 0.06 vs. 1.06 ± 0.08 vs. 1.10 ± 0.13, P=0.005), as did the lateral-Mid-BA angle(23.18 ±9.53 vs. 26.05 ±10.10 vs. 31.07 ±15.12, P=0.007) and the BAVA angle(32.98 ±17.85 vs. 34.51 ±17.96 vs. 41.51 ±19.22, P=0.024). There was a relatively weak positive correlation between altitude and the tortuosity of BA (rs=0.190 ,P=0.005), the lateral-Mid-BA angle (rs=0.201, P=0.003), the BA-VA angle (rs=0.183, P=0.006) with significant difference. Compared with group A and B, there were more multi-bending groups and fewer Oligo-bending groups in group C. (P<0.001). There was no difference in the VAH, actual length of BA, VAVA angle and the APMidBA angle among the three groups. Conclusion: With the increase in altitude, the tortuosity of BA and the sagittal angle of vertebrobasilar arterial system increased, and more VA multi-bending groups. The increase in altitude can lead to the changes in vertebrobasilar geometry.